2019
DOI: 10.1186/s12886-019-1144-8
|View full text |Cite
|
Sign up to set email alerts
|

Anterior chamber depth — a predictor of refractive outcomes after age-related cataract surgery

Abstract: Background Anterior chamber depth (ACD) is becoming a hot topic and plays an important role in correcting the refractive errors (REs) after cataract surgery. The aim of this study was to assess the ACD changes and their relationship with the REs after phacoemulsification and intraocular lens (IOL) implantation in patients with age-related cataracts. Methods One hundred forty-five eyes of 125 age-related cataract patients from the Department of Ophthalmology, Tangdu Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 33 publications
2
43
1
1
Order By: Relevance
“…In previous studies, acrylic IOLs are characterized by less anterior capsule contraction and less or the same decentration compared with PMMA and silicone IOLs [ 25 , 26 , 27 , 28 , 29 ]. Although some studies have investigated anterior chamber depth in eyes before and after IOL implantation [ 30 , 31 , 32 , 33 ], the measurements of the biomechanical characteristics of the IOLs based on the anterior displacement force of the IOL are unique in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, acrylic IOLs are characterized by less anterior capsule contraction and less or the same decentration compared with PMMA and silicone IOLs [ 25 , 26 , 27 , 28 , 29 ]. Although some studies have investigated anterior chamber depth in eyes before and after IOL implantation [ 30 , 31 , 32 , 33 ], the measurements of the biomechanical characteristics of the IOLs based on the anterior displacement force of the IOL are unique in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies [8][9][10][11][12] reported on the positive correlation of binocular RE after sequential cataract surgery and effectiveness of adjusting the target RE in the second eyes by correcting 50% of the errors from the first eyes for improving visual quality. The authors [10,13] speculated that this finding may be attributed to the revision of predictive errors from post-operative ACD. However, in China there are few reports on the calculation methods of IOL power for the second eyes of patients who underwent bilateral sequential cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing expectation for post-operative visual quality, the focus of the operation is not only safety, but also the best possible visual recovery. Many studies [13,24,25] suggested that refractive status was stable one month after operation, and refractive status shorter than this term should not be used as the basis for correcting the corresponding eye. Based on these clinical observations, bilateral surgery should be performed over 4 weeks, rather than simultaneously or in a short time span [26].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies [8][9][10][11][12] reported on the positive correlation of binocular REs after sequential cataract surgery and effectiveness of adjusting the target RE in the second eyes by correcting 50% of the errors from the first eyes for improving visual quality. Scholars [10,13] speculated that this finding may be attributed to the revision of predictive errors from postoperative ACD. However, in China there are few reports focused on this.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing expectation for post-operative visual quality, the focus of the operation is not only safety, but also the best possible visual recovery. Many studies [13,25,26] suggested that refractive status was stable one month after operation. Thus, bilateral surgery should be performed over 4 weeks, rather than simultaneously or in a short time span [27].…”
Section: Discussionmentioning
confidence: 99%